Prevalence and Factors Associated with Insomnia in Military Personnel: A Retrospective Study during the Second COVID-19 Epidemic Wave in Peru - Valladares-Garrido, Mario J. (2022)
Studies in military personnel are scarce and have reported increased rates of medical con-sultations and insomnia. The COVID-19 pandemic has been associated with a number of factors thatincrease the prevalence of insomnia, which has established consequences in the military. However,reported data are from different settings. We aimed to identify the prevalence and factors associatedwith insomnia during the second COVID-19 epidemic wave in Lambayeque, Peru. A retrospectivestudy in 566 participants was conducted face-to-face in November 2021. The dependent variable wasinsomnia, measured with the Insomnia Severity Index. The independent variables were socio-laborvariables, physical activity, food insecurity, eating behavior disorder, fear of COVID-19, and resilience.The prevalence of insomnia was 23% (95% CI: 19.6–26.7%). In multivariate analysis, insomnia wasassociated with a personal history of mental health (PR: 1.71, 95% CI: 1.01–2.93), food insecurity(PR: 1.43, 95% CI: 1.05–1.95), fear of COVID-19 (PR: 2.57, 95%CI: 1.87–3.54), and high resilience(PR: 0.60, 95%CI: 0.42–0.86). Overall, the Peruvian military population presents a high prevalenceof insomnia during the pandemic period. Special attention should be paid to factors that influenceinsomnia. Prevention and promotion programs should be established to reverse this negative trendin the military.